CLINICAL-EPIDEMIOLOGICAL CHARACTERISTICS AND LABORATORY MARKERS OF ACUTE BRUCELLOSIS IN THE KASHKADARYA REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This paper presents the results of a study on the characteristics of the course of acute brucellosis in the Republic of Uzbekistan. Data analysis was conducted on 120 patients selected from 178 individuals presenting with clinical signs of infection. A predominance of males was established among the cases (75.00%), which is attributed to the specifics of regional animal husbandry. The work details the routes of infection, gender differences in clinical manifestations, such as sacroiliitis, and key hematological changes.